El flâneur y la flanerie en el costumbrismo español. - Cuvardic García, Dorde (2012)
The purpose of this article is to show the importance of costumbrist  flâneur literature in the development of this aesthetic movement in Spain. The dimensions of the flâneur and of flanerie are analyzed in writings by Larra and Mesonero Romanos: a curious attitude towards public spaces, physical distancing, identification of urban social types, leisure behavior, semiotic metaphore use of the city as an open book, fragmented perception of urban diversity. In this article relations are also established with the European costumbrist literature of the time (France, Germany, England).